ESPECIFICAÇÃO E MODELAGEM DE PROCESSOS DE UM SISTEMA INTELIGENTE DE PREGÃO ELETRÔNICO - Carvalho, Christian Diniz (2011)
The Intelligent Electronic Auction System (SIPE) is an e-commerce system based on intelligent agent technology, which focuses Business to negotiations of the type of government. It arises in order to be a future alternative to the current procurement system of goods and services of Brazilian Public Administration - ComprasNet. Its main advantage is the semi automated of the negotiation process and automate the search for trading partners. And to demonstrate the feasibility of the methodology, we will apply the SIPE Business Process Management in making the business model of Electronic Auction held in traditional ComprasNet and also in the bidding process heldin the system proposed here.